High Throughput Screening of Nanoparticle Flotation Collectors - Abarca, Carla (My University, 2017)
The selective separation of valuable minerals by froth flotation is a critical unit operation in mineral processing. Froth flotation is based on the ability of chemical reagents, called collectors, to selectively lower the surface energy of valuable mineral particles, facilitating attachment of the modified mineral particles to air bubbles in the flotation cell. The mineral laden bubbles rise to the surface forming a froth phase that can be isolated. Novel cationic polystyrene nanoparticle collectors have been developed recently to be used as effective flotation collectors, aiming to recover challenging nickel sulfide ores that respond poorly to conventional molecular flotation collectors. However, optimizing nanoparticle flotation collectors is a challenge. An effective nanoparticle collector candidate should meet three requirements: (1) it should be colloidally stable in the flotation media; (2) it should be hydrophobic enough to change the mineral surface and induce an air bubble-mineral particle attachment; and (3) specifically and strongly bind to metal-rich minerals. Producing nanoparticles that are simultaneously colloidally stable and sufficiently hydrophobic presents a problematic task. Thus, a delicate balance of nanoparticle properties is required for commercially viable nanoparticle collectors. This thesis presents a promising approach for discovering and characterizing novel nanoparticle collectors by using high throughput screening techniques. Developed was a workflow for fast fabrication and testing of nanoparticle candidates, including: (1) parallel production of large nanoparticle libraries covering a range of surface chemistries, (2) a high throughput colloidal stability assay to determine whether a nanoparticle type is stable in flotation conditions; (3) an automated contact angle assay to reject nanoparticles that are not hydrophobic enough to induce efficient bubble-particle attachment, and; (4) a laboratory flotation test in sodium carbonate (pH~10) with the best nanoparticle candidates. The automated colloidal stability assay was based on the optical characterization of diluted nanoparticle dispersions in multiwell plates, yielding critical coagulation concentrations (CCCs) of sodium carbonate. To pass this screening test, the CCC of candidate nanoparticles must be greater than the effective carbonate concentration in commercial flotation cells. Since the nanoparticle size affects the intrinsic light scattering properties of the nanoparticles, two routes were developed. The colloid stability assay was suitable for nanoparticles ranging between 50 nm and 500 nm, since nanoparticle size. The automated contact angle assay used a miniature 16-well plate format where flat glass slides were exposed to 200 μL nanoparticle dispersions. The cationic nanoparticles formed a saturated adsorbed monolayer on the glass, and after rinsing and drying, the water contact angle was automatically measured. Effective nanoparticle candidates had contact angles greater than 50 degrees, a criterion developed with model experiments. During the development of the automated workflow platform, a series of nanoparticles with methyl-ended PEG-methacrylate monomers were prepared. Although the PEG chains greatly enhanced colloidal stability, the particles were too hydrophilic to be effective collectors. Interestingly, nanoparticles with long PEG chains acted as froth modifiers, giving wetter and more robust foams as well as increased entrainment of materials that did not adhere to bubbles. Conventional laboratory scale latex synthesis methodologies are far too inefficient to generate large library of candidate nanoparticles. Instead, we started with a few parent nanoparticle types and then used Click chemistry to generate a large range of surface chemistries. Specifically copper-mediated azide alkyne cycloaddition reaction was used to functionalize the surface of azide nanoparticles with different chemical groups, ranging from hydrophilic amine-terminated PEG chains, to hydrophobic hexane-terminated materials. The Click library exhibited an extensive range of critical coagulation concentrations and contact angle values. For example, for a given parent azide nanoparticle, the contact angles ranged from 62 to 101 degrees, depending upon the density and type of click reagent. A novel paper chromatographic method was developed for the quantitative determination surface azide. This assay was critical for determining the surface density of functional groups from the click reactions. Overall, high throughput screening techniques were designed and applied to the development of nanoparticle collectors for froth flotation. Automated screening assays of critical coagulation concentration and contact angle proved to be effective in obtaining flotation domain maps, and finding the most promising nanoparticle collectors for froth flotation. I believe the work in this thesis is one of the first reported uses of high throughput methodologies for the development of mineral flotation reagents.
Carla Abarca Ph.D. Thesis
Keywords: Nanoparticle Flotation Collectors; High Throughput Screening; Nanoparticles; Flotation; High Throughput; Click Chemistry